2003
DOI: 10.1021/jf034466n
|View full text |Cite
|
Sign up to set email alerts
|

Black Rice (Oryza sativa L. indica) Pigmented Fraction Suppresses both Reactive Oxygen Species and Nitric Oxide in Chemical and Biological Model Systems

Abstract: Anthocyanins, present in fruits and vegetables as natural colorants, have been well characterized to possess bioactive properties. Anthocyanin components extracted from black rice (Oryza sativa L. indica) separated by gel filtration and identified using LC-MS were cyanidin 3-glucoside and peonidin 3-glucoside. A standardized extract of black rice pigmented fraction (BRE) containing known proportions of cyanidin 3-glucoside and peonidin 3-glucoside exhibited marked antioxidant activities and free radical scaven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
213
1
9

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 322 publications
(232 citation statements)
references
References 37 publications
9
213
1
9
Order By: Relevance
“…In addition to vitamin A derivatives, there are many additional chemopreventive compounds that have elicited a variety of cancer preventing effects including induction of apoptosis, stimulation of differentiation and suppression of cell proliferation in both in-vitro and in-vivo models (25)(26)(27)(28). Relevant to this current study, compounds which provide natural colors to fruits and vegetables such as the anthocyanins, have been shown to demonstrate a wealth of chemopreventive properties (15,(27)(28)(29)(30). While anthocyanins represent the primary flavinoids in FBR, black raspberries also contain additional chemopreventive compounds including ferulic acid, coumaric acid, quercetin, and phtyosterols.…”
Section: Discussionmentioning
confidence: 92%
“…In addition to vitamin A derivatives, there are many additional chemopreventive compounds that have elicited a variety of cancer preventing effects including induction of apoptosis, stimulation of differentiation and suppression of cell proliferation in both in-vitro and in-vivo models (25)(26)(27)(28). Relevant to this current study, compounds which provide natural colors to fruits and vegetables such as the anthocyanins, have been shown to demonstrate a wealth of chemopreventive properties (15,(27)(28)(29)(30). While anthocyanins represent the primary flavinoids in FBR, black raspberries also contain additional chemopreventive compounds including ferulic acid, coumaric acid, quercetin, and phtyosterols.…”
Section: Discussionmentioning
confidence: 92%
“…This showed that the antioxidant compounds present in these grains might act in different ways to reduce the oxidative stress in the organism and, with that, help in the prevention of several diseases. The reduction of the oxidative stress by polyphenols in rice grains was observed in in vitro and ex vivo studies, indicated by the reduction in the production of nitric oxide (Hu et al, 2003) and in the concentration of reactive oxygen species (Hu et al, 2003;Chiang et al, 2006). Simultaneously to the reduction in the indicators of oxidation, an increase in the antioxidant capacity was observed, including higher total antioxidant capacity and increased activity of antioxidant enzymes, such as superoxide dismutase and catalase .…”
Section: Antioxidant Activity and Biological Effectmentioning
confidence: 94%
“…In rice grains with red and black pericarp, the main phenolics are the anthocyanins cyanidin-3-O-β-Dglucoside and peonidin-3-O-β-D-glucoside (Oki et al, 2002;Hu et al, 2003;Chen et al, 2006;Zhang et al, 2006;Yawadio et al, 2007). Other compounds identified include the anthocyanidins cyanidin and malvidin (Hyun and Chung, 2004;Zhang et al, 2006), the anthocyanins pelargonidin-3,5-diglucoside and cyanidin-3,5-diglucoside (Zhang et al, 2006) and phenolic acids, like ferulic, caffeic and protocatechuic acids (Morimitsu et al, 2002).…”
Section: Phenolic Compounds In Ricementioning
confidence: 99%
See 2 more Smart Citations